Analysis of the formation of filament winding in terms of force interactions between threads - Nuriyev, Mahamadali; Veliev, Fazil; Seydaliyev, Ilham Mammad; Dadashova, Kamala; Jabbarova, Ganira Zargar; Allahverdiyeva, Ilhame (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated a problem of filament winding formation in terms of force interactions between threads. It was established that at certain ratios between the frequency of bobbin rotation and the frequency of thread feeder motion the threads are laid on the same place. This results in the formation of the so-called filament winding. In this case, in an extreme case, a turn of the thread is laid exactly on the place of the preceding one. This phenomenon, however, occurs only if the thread is considered ideal, that is, it has no thickness. It is shown that due to sufficient complexity of actual processes a thread cannot be placed exactly on the place of the one laid earlier, which results in that it flies off it. In this case, the turn laid earlier acquires the role of a spreader, that is, it defines the place of laying a thread on the bale. This place can differ significantly from that set by the motion of a thread feeder, resulting in the formation of chords, which cause breaks of thread at subsequent unwinding of the bobbin. It is proposed, in order to eliminate the specified defects of winding in the form of filaments and chords that accompany them, to reduce to the permissible minimum the distance from the eye of a thread feeder to the point of attack. We describe conditions under which a fly-off of the turn occurs, based on which it becomes possible to determine the number of turns, laid with a breach of the kinematic conditions, as one of the basic parameters of the process. The latter means that there is no need for the thread feeder to control it. It is shown that a given parameter depends on the inclination angle of the turn, and the application of the resulting analytical description of this relation does not present any practical difficulties because all actual values of its constituent magnitudes, except for thread twisting stiffness, are known when designing a winding mechanism. It was established that in addition to the proposed design solution it is necessary to maintain the tension not less than 20 sN for the yarn 225´2 tex. In the case of other linear densities, this parameter can be calculated based on the obtained analytical dependences for a thread inclination angle and duration of torsional oscillations of a homogeneous rod suspended in the middle. Such results form the basis of requirements to the design of a winding mechanism, which are aimed at reducing the number of uncontrollably placed turns.